SPEAKING ACTIVITIES IMPLEMENTED IN AN ENGLISH CLUB: STUDENTS’ VOICES - Mahran Abdi Maros; Ridha Ilma; Renny Kurniasari (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2023)
AnEnglish club has many important goals to support the fluency of students in mastering English skills, especially in speaking skills. Sometimes, it brings positive and negative drawbacks to the students with some activities provided. The study aimed to find out how students felt about the different types of speaking activities that were hosted by the English club. Qualitative research approaches were utilized in this case study approach to research. The participants were three students who were members of the English club at one of senior high schools in Palembang. The information was acquired by conducting an interview that was semi-structured and using open-ended questions. The data were evaluated by employing a methodology known as theme analysis. The outcomes of the study revealed that (a) debate activity did not improve speakers' pronunciation, comprehension, or grammar, (b) speech activity assisted the students' speaking components, which included pronunciation, vocabulary, comprehension, fluency, and grammar in the process of speaking, (c) students were able to practice English speaking skills such as pronunciation, vocabulary, comprehension, fluency, and grammar through story-based activities, (d) activities related to newscasting did not aid the student in instructing and learning vocabulary.